Let's Play!: a story role-play Kit to foster social skills among children living with Autism Spectrum Disorder - Lim, Daphne (2017)
Children living with Autism Spectrum Disorder often find it difficult to cope with their social environment. This design research project seeks to foster social skills among children living with Autism Spectrum Disorder through the mode of play. This interdisciplinary project has engaged Rainbow Centre, Margaret Drive to inform design development. This included engaging their professional feedbacks on the design and user testing at appropriate stages in order to ensure the overall effectiveness of the final outcome. In doing so, it explored the dynamics between designers and educators in the special needs community in improving the social skills of children on the spectrum. At the end of the project, a story role-play kit is developed for use in Autism Schools to promote the learning and development of social skills in students living on the spectrum. With the help of visual narrative and role-playing activities, the learning play kit facilitates understanding, allowing the effective learning for these students. By introducing and lending design skills, this design research project also helps facilitate teachers in the teaching of social skills to students in Autism schools. Lastly, it provides an opportunity to move students with Autism Spectrum Disorder from a repetitive, solitary pattern of play to one that promotes interaction with their peers and teachers.